Inhibition of Rho-kinase protects cerebral barrier from ischaemia-evoked injury through modulations of endothelial cell oxidative stress and tight junctions - Gibson, Claire L.; Srivastava, Kirtiman; Sprigg, Nikola; Bath, Philip M.W.; Bayrakutan, Ulvi (Wiley, 2014)
Ischaemic strokes evoke blood–brain barrier (BBB) disruption and oedema formation through a series of mechanisms involving Rho-kinase activation. Using an animal model of human focal cerebral ischaemia, this study assessed and confirmed the therapeutic potential of Rho-kinase inhibition during the acute phase of stroke by displaying significantly improved functional outcome and reduced cerebral lesion and oedema volumes in fasudil- versus vehicle-treated animals. Analyses of ipsilateral and contralateral brain samples obtained from mice treated with vehicle or fasudil at the onset of reperfusion plus 4 h post-ischaemia or 4 h post-ischaemia alone revealed these benefits to be independent of changes in the activity and expressions of oxidative stress- and tight junction-related parameters. However, closer scrutiny of the same parameters in brain microvascular endothelial cells subjected to oxygen glucose deprivation ± reperfusion revealed marked increases in prooxidant NADPH oxidase enzyme activity, superoxide anion release and in expressions of antioxidant enzyme catalase and tight junction protein claudin-5. Cotreatment of cells with Y-27632 prevented all of these changes and protected in vitro barrier integrity and function. These findings suggest that inhibition of Rho-kinase after acute ischaemic attacks improves cerebral integrity and function through regulation of endothelial cell oxidative stress and reorganization of intercellular junctions.